ANALISIS KEBUTUHAN PENGEMBANGAN EBOOK BERBASIS LITERASI SAINS DALAM PEMBELAJARAN FISIKA - Sari, Siska Arinda; Ismet, Ismet; Kistiono, Kistiono (Universitas Negeri Surabaya, 2023)
This research is survey research to analyze the needs of teachers and students for learning reference sources in the form of ebooks. This research is a part of development research, namely in the preliminary stage. Scientific literacy-based ebooks are ebooks that will be developed. The development of scientific literacy-based ebooks aims to help students understand physics material and can be used as a learning reference source besides school textbooks. The instrument in this study was a questionnaire. The questionnaire was then distributed using the Google form to high school physics teachers and high school students. Students need ebooks as a learning resource that can be opened through communication tools such as mobile phones. So that it can help students understand physics material and can learn practically anywhere. In addition, ebooks based on scientific literacy are expected to arouse students reading interest which is classified as low. Students' knowledge of science becomes wider and follows developments in the world of science from time to time. Keywords: Ebook, Scientific Literacy, Needs Analysis, Physics Learning